2018
DOI: 10.1016/j.cej.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent mannose-decorated NIR nanoprobes for targeting pan lymph nodes

Abstract: Lymphadenectomy is a prerequisite for most malignancies to define the precise staging of cancer, as well as resect the possible metastases completely. While it improves prognosis, lymphadenectomy often causes postoperative edema or bleeding because of unclear surgical margins. In this study, we synthesized near-infrared (NIR) fluorescent nanoprobes with conjugating various mannose moieties on the surface to target macrophages in the lymph node. Armed with these NIR nanoprobes, we demonstrated the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…Therefore, mannose-conjugation is a promising approach for targeting macrophages through specific recognition by the MMR [18,19,20]. To date, various mannose-conjugated proteins, polymers, nanoparticles, liposomes, and imaging probes have been developed for treating and diagnosing various diseases, such as cancer, infectious diseases, and metabolic diseases [21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mannose-conjugation is a promising approach for targeting macrophages through specific recognition by the MMR [18,19,20]. To date, various mannose-conjugated proteins, polymers, nanoparticles, liposomes, and imaging probes have been developed for treating and diagnosing various diseases, such as cancer, infectious diseases, and metabolic diseases [21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorophores are representative light-responsive materials, which absorb light energy and emit photons with particular wavelengths [3,39]. By simple loading or conjugating dyes to the targeting domain, such as small molecule ligands, peptides, proteins, antibodies, and polymers, many imaging nanoprobes have been developed and applied in bioimaging and therapy [7,9,40ā€“46]. Atreya et al conjugated fluorescein isothiocyanate (FITC) on an adalimumab antibody for in vivo imaging of membrane-bound tumor necrosis factor (mTNF) [47].…”
Section: Light-responsive Nanomaterialsmentioning
confidence: 99%
“…Byeon et al reported cationic-and mannose-modified-albumin NPs for treatment of brain tumors. [95] In this case, mannose moieties as mimics of glucose, are ablet oh elp modified NPs cross the blood-brain barrierb ym eanso ft he glucoset ransporter 1( GLUT1) and GLUT3 pathways, [96] which are responsible for the import of glucose and fructose as energy supplies. Mannose has also been reported as one of the hexoses transported by the GLUT family, [97] which can be considered as an alternative targeting strategy.…”
Section: Mannose-based Nanomaterials In Other Applicationsmentioning
confidence: 99%
“…Byeon et al. reported cationicā€ and mannoseā€modifiedā€albumin NPs for treatment of brain tumors . In this case, mannose moieties as mimics of glucose, are able to help modified NPs cross the bloodā€“brain barrier by means of the glucose transporter 1 (GLUT1) and GLUT3 pathways, which are responsible for the import of glucose and fructose as energy supplies.…”
Section: Mannoseā€based Nanomaterials In Biomedical Applicationsmentioning
confidence: 99%